2001
DOI: 10.1086/319681
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Th2 Cytokines Decreases the Development of and Improves Behçet's Disease–Like Symptoms Induced by Herpes Simplex Virus in Mice

Abstract: In the etiology of Behçet's disease (BD), viral infection has long been postulated as a contributing factor, and viral involvement has been demonstrated. However, viral infection alone is not sufficient to explain the pathogenesis of BD, and some evidence suggests that immunologic abnormalities are also important. To study the possible role of immune regulation in the development of BD-like symptoms induced by herpes simplex virus inoculation in ICR mice, macrophages were deleted by use of liposome-encapsulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“…The lower incidence of Behçet's diseaselike symptoms in Balb/c mice might be related to the production of higher IL-10 level and lower IFN-g level, contrary the higher incidence in C57BL/6 is dependent on higher IFN-g level and lower IL-10 level. This result matched our previous experiment that Th1/Th2 cytokine expression could regulate the development and attenuation of Behcet's disease-like symptoms in ICR mice [35].…”
Section: Discussionsupporting
confidence: 91%
“…The lower incidence of Behçet's diseaselike symptoms in Balb/c mice might be related to the production of higher IL-10 level and lower IFN-g level, contrary the higher incidence in C57BL/6 is dependent on higher IFN-g level and lower IL-10 level. This result matched our previous experiment that Th1/Th2 cytokine expression could regulate the development and attenuation of Behcet's disease-like symptoms in ICR mice [35].…”
Section: Discussionsupporting
confidence: 91%
“…Thus, Th2 cytokine expression may be involved in attenuation of the symptoms of BD. In accordance with our findings, it was reported that depletion of macrophages suppressed BD-like symptoms and the suppression was correlated with IL-4 expression in splenocytes in the BD model of ICR mice [35]. Taken together, it is possible that the Th1 shift first occurred in BD via Txk overexpression in CD4+ T cells and Th2 cytokine production was modified to attenuate the inflammatory conditions.…”
Section: Th1/th2 Responsessupporting
confidence: 91%
“…It was later shown to also be expressed on Th17 cells (Hastings et al 2009). A strong Th1 immune response occurs in active BD and contributes to the prolonged inflammatory condition of BD (Frassanito et al 1999;Sohn et al 2001). Recently, highly expressed Th17 was also found to be related to inflammation in BD-like mice (Shim et al 2009).…”
Section: Discussionmentioning
confidence: 99%